Insider and Out: Making Sense of a Prison Experience and a Research Experience. (April 2014) - Earle, Rod
Prison ethnographers in the United Kingdom have offered rich and diverse accounts of penal interiors, and prisoners' views and experiences have been, for the most part, reported with sensitivity, creativity, and insight. In the midst of this relatively flourishing qualitative research activity, the actual voices prisoners, and of ex-prisoners who are now prison researchers, have been relatively subdued, although there are signs that this may be about to change. In this article, I explore some of the potentials, possibilities, and problems afforded by insider research—that is, research that draws on direct experience of penal confinement—and explore whether, and how, "spending time" is different from "serving time." As opportunities to "do prison research differently" emerge, I critically examine some of the epistemological claims and potentials of insider research, its relations to ethnography, and the relevance of advocacy groups, such as Convict Criminology.